PENGARUH KOMPENSASI, LNGKUNGAN KERJA DAN MOTIVASI TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Yohannes Vemberi; Lucia Ika Fitriastuti (Sekolah Tinggi Ilmu Ekonomi SBI, 2015)
The purpose ofthis research is to examine the effect ofcompensation (direct and indirect compensation), work environment, and motivation on job satisfaction. Then examine the effect ofjob satisfaction on employee performance. The researcher.s used questionnaires to obtaining the data in this study. The questionnaire measures the five variables, compensation, work environment, motivation, job satisfaction and employee per- formance. Respondents are already working in a company. This research using 65 samples. The data analysis used regression analysis. These results indicate that the compensation (direct and indirect) influence employee satisfaction. Work environment does not affect employee satisfaction. Motivation affects employee satisfaction. Job satisfaction affects employee performance.